Transient Frequency Spectrum Analysis for Single Line-to-Ground Fault Location in Insulated Power Systems - Shepel, Oleksandr; Matsui, Anatolii (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This paper addresses the critical challenge of accurately locating Single Line-to-Ground (SLG) faults in insulated electrical power systems. The authors argue that traditional steady-state measurement methods are unreliable in these systems because the fault current is minimal, making it highly sensitive to high fault resistance and difficult to measure against background noise. To overcome this, the paper proposes Transient Frequency Spectrum Analysis (TFSA), which utilizes the high-frequency transient components of the zero-sequence voltage (V0​) and current (I0​) generated at the moment the fault occurs. Since these transients are largely independent of the fault resistance, TFSA offers significantly higher accuracy. Crucially, the authors identify that existing Digital Fault Recorders (DFRs) in Ukrainian substations are unsuitable for TFSA due to their limited bandwidth and, most notably, the absence of a hardware fundamental frequency filter. This filter is essential because the high-amplitude fundamental frequency component consumes the ADC's resolution, masking the required high-frequency transient data. To enable the practical deployment of TFSA, the paper concludes by detailing the successful design and development of a custom DFR prototype with a wide bandwidth and a dedicated analog fundamental frequency filter. — Ця стаття присвячена критично важливому завданню точного визначення місця однофазного замикання на землю (ОЗЗ) в ізольованих електричних енергосистемах. Автори стверджують, що традиційні методи вимірювання сталого режиму є ненадійними в таких системах, оскільки струм замикання є мінімальним, що робить його високочутливим до великого опору в місці замикання та ускладнює вимірювання на тлі фонового шуму. Для подолання цього недоліку в статті пропонується Аналіз перехідного частотного спектру (АПЧС), який використовує високочастотні перехідні складові напруги нульової послідовності (V0​) і струму нульової послідовності (I0​), що генеруються в момент виникнення замикання. Оскільки ці перехідні процеси значною мірою не залежать від опору в місці замикання, АПЧС забезпечує значно вищу точність. Важливо, що автори виявили, що існуючі Цифрові реєстратори аварійних подій на українських підстанціях не придатні для АПЧС через їх обмежену смугу пропускання і, особливо, відсутність апаратного фільтра основної частоти. Цей фільтр є необхідним, оскільки високоамплітудна складова основної частоти споживає роздільну здатність АЦП (аналого-цифрового перетворювача), маскуючи необхідні високочастотні перехідні дані. Щоб уможливити практичне впровадження АПЧС, стаття завершується детальним описом успішної розробки та створення прототипу власного пристрою із широкою пропускною смугою та спеціалізованим аналоговим фільтром основної частоти.